Restoring efforts of the Brazilian Telecommunications R&D: A Regulatory Theory Approach - Scholze, Simone Henriqueta Cossetin (Law, State and Telecommunications Review, 2013)
Purpose ”“ The purpose of this study is to examine initiatives adopted by the Brazilian regulatory agency in support of R&D activities in the Brazilian telecommunications, in the light of some regulatory theories, particularly incentive regulation. Methodology/approach/design ”“ The telecommunications reform in Brazil from the end of the 1990s up to Anatel’s current activities are seen through a fact and law approach. Analysis is made of regulatory theories that have been projected over the course of state action in the economic field, such as the theory of the public interest. Findings ”“ The application of the study of Robert Horwitz may be useful for further commensurability consideration of U.S. and Brazilian state regulation models. Practical implications ”“ This critical analysis seeks to provide an overview and an introductory approach that offers a starting point for further knowledge deepening of the interactions between state regulation and R&D public policies. Originality/value ”“ The text proposes a contribution towards identifying elements in the legal-institutional and theoretical sphere that allow for a renewed view over the reasons and the legitimacy of such unprecedented role taken by the Brazilian regulatory body in the field of R&D.